2009
DOI: 10.1590/s0103-05822009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e antropometria em pacientes com paralisia cerebral hemiplégica

Abstract: Objective: To analyze the linear growth, the head circumference and the anthropometric differences between involved and non-involved sides of 24 children with hemiplegic cerebral palsy, comparing them to standard values for age.Methods: This cross-sectional study enrolled 24 consecutive children with cerebral palsy clinically classified as spastic hemiplegia. The anthropometric measures included: weight, lenght, head circumference, total upper limb length, hand length, palm width, total lower limb length, foot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Differently from these last-mentioned studies, the study Zonta et al [ 30 ] with children with hemiplegic paralysis aged 3 to 5 years indicated averages of weight, height, and cephalic perimeter that were adequate for age with 21% of the finding of microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from these last-mentioned studies, the study Zonta et al [ 30 ] with children with hemiplegic paralysis aged 3 to 5 years indicated averages of weight, height, and cephalic perimeter that were adequate for age with 21% of the finding of microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…In an anthropometric analysis, Watemberg, Silver, Harel et al (2002) observed, by analyzing and measuring the head circumference of children with CP that 15.4% of the patients showed below average measurements, which is considered one of the main diagnoses associated with microcephaly. Studies about the head circumference's growth parameters related to all of the clinical forms of CP show that these measurements are significantly lower in cases of tetraplegia and hemiplegia, compared to healthy individuals (ZONTA, AGERT, MUZZOLON et al, 2009). According to Pelegano (1976), these restrictions on growth stimuli of the craniomandibular structure around the TMJ region may condition and worsen muscle groups' reduced activity, including lateral pterygoid muscles affected by hypertonia brought upon by CP.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of linear growth and head circumference twenty-four children with cerebral palsy spastic type hemiplegia, it was found that 10% were less than ideal height for age and weight were too. 20 The etiology of growth retardation of children with chronic diseases such as PC is multifactorial and may be related to non-nutritional factors resulting from brain malformations or lesions responsible for the inability of child. 21 The type of movement disorder, the severity the PC involvement, especially in relation to self-feeding, the ability to walk, and the degree of limitation in physical activity have been identified as factors that influence changes in growth.…”
mentioning
confidence: 99%